PENERAPAN METODE GERAK TANGAN UNTUK MENINGKATKAN INGATAN SISWA DALAM MENGHAFAL LAFADZ DAN TERJEMAHAN SURAH AL-QADR - Demolinsara, Demolinsara; Munir, Muhammad (LP2M STAI Darul Kamal NW Kembang Kerang, 2021)
Abstract The purpose of this study is to describe improving students' memory in memorizing lafadz and translation of Surah Al-Qadr through the application of the hand movement method in learning Al-Qur'an Hadith at MI NW Kalijaga. The subjects of this research were 14 students of class VB. This type of research is Classroom Action Research (CAR) which uses the Kemmis & Mc Taggart (1998) model, each cycle consisting of four steps, namely (1) planning, (2) implementation, (3) observation and (4) reflection. Data collection techniques using observation, documentation, and tests. The data were analyzed by means of descriptive qualitative and descriptive quantitative. The results showed that the hand gesture method could improve students' memorization of the Al-Qur'an Hadith subjects in the Al-Qadr surah material. In the pre-cycle, it showed that out of 14 students, only 4 students had fulfilled the KBM (72%) with an average score of 58.57 and a percentage of 29%. Cycle I there is an increase in completeness to 7 students with an average value of 61.07 and a percentage of 50%. In the second cycle the increase increased to 12 students with an average value of 83.28 and a percentage of 86%.